Seven days in June [compact disc, unabridged] : a novel - Williams, Tia, 1975- (Hachette Book Group, 2021)
Brooklynite Eva Mercy is a single mom and bestselling erotica writer. Shane Hall is an enigmatic, award-winning author who shows up in New York. When Shane and Eva meet at a literary event, sparks fly.